Human Amniotic Fluid Stem Cell-Derived Exosomes as a Novel Cell-Free Therapy for Cutaneous Regeneration - Zhang, Yan; Yan, Jiaqing; Liu, Yanhong; Chen, Zhenyu; Li, Xiheng; Tang, Liang; Li, Jiang; Duan, Mengna; Zhang, Guokun (Frontiers in Cell and Developmental Biology, 2021)
Adult wound healing often results in fibrotic scarring that is caused by myofibroblast aggregation. Human amniotic fluid stem cells (hAFSCs) exhibit significantly anti-fibrotic scarring properties during wound healing. However, it is little known whether hAFSCs directly or indirectly (paracrine) contribute to this process. Using the full-thickness skin-wounded rats, we investigated the therapeutic potential of hAFSC-derived exosomes (hAFSC-exo). Our results showed that hAFSC-exo accelerated the wound healing rate and improved the regeneration of hair follicles, nerves, and vessels, as well as increased proliferation of cutaneous cells and the natural distribution of collagen during wound healing. Additionally, hAFSC-exo suppressed the excessive aggregation of myofibroblasts and the extracellular matrix. We identified several miRNAs, including let-7-5p, miR-22-3p, miR-27a-3p, miR-21-5p, and miR-23a-3p, that were presented in hAFSC-exo. The functional analysis demonstrated that these hAFSC-exo-miRNAs contribute to the inhibition of the transforming growth factor-β (TGF-β) signaling pathway by targeting the TGF-β receptor type I (TGF-βR1) and TGF-β receptor type II (TGF-βR2). The reduction of TGF-βR1 and TGF-βR2 expression induced by hAFSC-exo was also confirmed in the healing tissue. Finally, using mimics of miRNAs, we found that hAFSC-exo-miRNAs were essential for myofibroblast suppression during the TGF-β1-induced human dermal fibroblast-to-myofibroblast transition in vitro. In summary, this study is the first to show that exosomal miRNAs used in hAFSC-based therapy inhibit myofibroblast differentiation. Our study suggests that hAFSC-exo may represent a strategic tool for suppressing fibrotic scarring during wound healing.